On-chip topological THz biosensors - Navaratna, Nikhil (2023)
On-chip terahertz (THz) biosensors have enormous potential in advancing the development of integrable devices for real-time, label-free, and noninvasive detection of proteins, DNA, and cancerous tissue. However, high absorption of THz waves by water necessitates evanescent field-based biosensing. The conventional on-chip THz biosensors with small mode confinement volumes and scaling sensitivity to defects severely limit the interaction of analyte with the electromagnetic field. Here, we reveal a topological waveguide cavity system with topologically protected propagating interfacial modes, exhibiting evanescent waves with an out-of-plane field extent of 0.3 λ 0 , where λ 0 is the wavelength corresponding to the cavity resonance frequency. Our experiments involving biomolecule detection and leaf-hydration monitoring show that the near-field of high-Q topological cavity resonances accurately detects minute frequency shifts over extended periods, facilitating real-time sensing and monitoring of biological matter. Implementation of topologically protected evanescent fields in waveguide-cavity systems will enhance on-chip THz biosensing.